Aplikasi Pendukung Keputusan Bagi Siswa SMK Taman Siswa Sukoharjo Dalam Pemilihan Perguruan Tinggi Berbasis Web - Budi Hartanto, Wawan Laksito YS, Teguh susyanto (Jurnal Ilmiah SINUS, 2013)
The purpose of this study is to develop a decision support application for the selection of students in web-based college. With this application, a decision is expected to provide an alternative for students in selecting a college. The decision support method used is the method of Analytical Hierarchy Process (AHP). To be able to use this application service students must make the registration process first. In terms of programming language the author uses language program Hyper Text Preprocessor (PHP). The software supports the creation of applications that Macromedia Dreamweaver, Mysql, and Adobe Photoshop. Keywords: Decision Support Systems, AHP method, Choosing a College